New paleontological and stratigraphical data on the upper - cretaceous transgression of the Pelagonian zone s.l. (Marmeiko, Ptoon Mt. NE Beotia) - ΜΕΡΜΙΓΚΗ, Α.; ΜΑΡΚΟΠΟΥΛΟΥ - ΔΙΑΚΑΝΤΩΝΗ, Α.; ΖΑΜΠΕΤΑΚΗ - ΛΕΚΚΑ, Α. (Bulletin of the Geological Society of Greece, 2018)
This paper concerns the study of a transgressive series, which overlies the upperjurassic oolitic limestones of subpelagonian zone, as well as the lateritic deposits, resulting from the alteration of the ophiolitic and fill the karstic cavities of the above mentioned limestones in NE Beotia (Fig.l). The purpose of this study is to • elucidate the age of the transgression, that occurred on the Jurassic limestones of the pelagonian platform at this region. • Discuss about the observed diachronism of the Late Cretaceous transgression on the Pelagonian platform. It is based on the study of micro- and macrofauna occurred in a section we describe in the "Marmeiko" area, on the Ptoon mountain. NOETH (1931) was the first who defined as Upper Turonian the age of the transgressive series, based on the study of Rudists. Later, BIGNOT & GUERNET (1968) studied the microfauna and attributed an age of lower Senonian. STEUBER (1993) based on the study of Hippuritidae, defined as Turonian and later (1995) as Turonian - Coniacian the age of the transgessive series. The basal part of the series consists of marls and marly limestones alternations. An abundant micro and macrofauna is found in this part of the section, as well as the first Rudist biostrome. In the middle part of the section 2 Rudist biostroms alternate with bioclastic limestones, containing abundant microfauna. In the upper part marls alternate with cherty limestones. The determinated micro- and macrofauna (Fig. 1), precises the age of the transgressive series as Santonian. This result confirms the diachronism of the transgressive phenomenon on the Pelagonian Upper- Jurassic limestones and the overthrusted ophiolites (AUBOUIN et al. 1960, BRUNN et al. 1972, KALLERGIS & ALBANTAKIS 1970, MAVRIDIS et al. 1979, NOETH 1931, BIGNOT & GUERNET 1968, CLEMENT & FERRIERE 1973, BIGNOT et al. 1973, STEUBER 1993, 1995, SKARPELIS & ZAMBETAKIS – LEKKAS 1998)